Keragaan Ekonomi dan Faktor yang Mempengaruhi Penangkaran Benih Padi Binaan Program Desa Mandiri Benih di Sumatera Utara - Situmorang, Sawitania; Girsang, Setia Sari (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Stapple food subsector is the second largest contributor after plantations subsector to Indonesian gross domestic product (GDP). However, since 2015, the productivity has been declining, though still provides a positive value. To anticipate the simultaniously decline of the productivity, the government has socialized the Seed Self Sufficiency Village (3SV) Programe with paddy. One of the provinces that has has been received the implementation of this 3SV programe is North Sumatra. Therefore, this study aims to analyze the economic performance of 3SV fostered village’s rice seed growers such as: production costs, profitability and business efficiency as well as the factors that affect the fostered paddy seed’s growers. This research was conducted using a survey method from August to November 2019. Data was collected through interviews with 30 fostered paddy seed’s growers in the districts of Deli Serdang, Batu Bara, Langkat, Serdang Bedagai, Simalungun, and South Nias. The location was chosen deliberately while the respondent farmers were chosen by judgmental method. The level of profitability is calculated using Gross Profit Ratio (GPR) while technical efficiency is analyzed using the Stochastic Frontier Production Function. The results showed that the rice seedling business in the observed area was strongly influenced by area of land, the amount of use of seeds and additional fertilizers. Meanwhile, increasing the use of labor, basic fertilizers, Growth Regulator (GR), and pesticides will reduce the performance of the rice seedling business. The availability of irrigation water and farmer groups has a big influence in reducing technical inefficiencies.